Assessment of Efficacy and Safety Associated with COVID-19 Vaccines: A Questionnaire Based Cross-Sectional Study - Adusumilli, Sri Jahnavi; Gadu, Hari Sai Gnana Lakshmi; Marni, Devi Priyanka; Mudunuri, Sri Raghu Bapiraju (Indian Journal of Pharmacy Practice)
Objectives: To evaluate the effectiveness and safety of different COVID-19 vaccines approved by CDSCO. The aim is to assess the safety and efficacy of COVID-19 vaccines through a questionnaire-based cross-sectional study. Materials and Methods: The Cross-Sectional Observational study has been carried out through a questionnaire-based survey followed by a telephonic interview. Microsoft Excel and GraphPad Prism version 9.3.1 were accessed to examine the statistics. Chi-square, Kruskal-Walli’s, and Mann-Whitney tests were accessed to assess the effect of categorical variables, one independent variable on two or more dependent variables, and 2 independent groups respectively. Results: Significant difference seen between marital status and COVID infection status, age, and vaccination status. The older the age, number of vaccines taken increases. Significant differences were seen between age and severity of side effects. High-age people have less severe side effects. Vaccinated people were less infected with COVID-19 infection. Significant differences were seen between age and Covid infection status. Low-age people were less infected. Conclusion: In our study, 37.38% weren’t infected. Among the infected 65.69% were before vaccination, 10.51% after the first dose and before the second dose, 20.22% after the second dose, 1.94% after the booster dose, and 1.61% both before and after vaccination. 41.86% experienced side effects like fever, pain at the injection site, body pains, and headache. Side effects being temporary only a few had to stop by a physician or taken to the infirmary. So, we conclude COVID-19 vaccines have shown better efficacy and safety.
Keywords: SARS-CoV-2; COVID-19; AEFIn; CDSCO